Box-Based Temporal Decomposition of Multi-Period Economic Dispatch for Two-Stage Robust Unit Commitment - Cho, Youngchae; Ishizaki, Takayuki; Ramdani, Nacim; Imura, Jun-ichi (IEEE transactions on power systems, 2019)
To ensure the feasibility of a unit commitment (UC) schedule under uncertainty, most existing two-stage robust UC methods formulate their second-stage problems as a multi-period economic dispatch (ED) problem with dynamic constraints, which does not properly model real-time ED where dynamic constraints relevant to the future operation are not certifiable. This paper proposes a two-stage robust UC method where a UC schedule and a box in a feasible operation set of each power source as its new feasible operation set are determined. As the multi-period ED problem with the refined feasible set at the second stage has no dynamic constraint, it is identical to a series of single-period ED problems. By modeling real-time ED as the single-period ED problems whose solutions depend only on uncertainties at the corresponding timeslots, the proposed method presents a practical framework of non-anticipative robust UC. Simulation results with a 118-bus system demonstrate the performance of the proposed method.